Implementation of PSAK 45 in Financial Reporting of the NTB Transportation Agency as an Effort to Increase Transparency and Accountability - Ulfa Tiana (Cita konsultindo, 2024)
In the era of globalization and increasingly fierce competition, transparency and accountability in government agency financial reporting has become very important. The implementation of accounting standards that are appropriate to regional conditions, such as PSAK 45, is the main basis for achieving openness and accountability in the government sector. This research aims to increase transparency and accountability in the financial reporting of the NTB Transportation Service through the implementation of PSAK 45. This research methodology uses a qualitative approach with descriptive analysis. The data collected were the financial reports of the NTB Transportation Service which were then analyzed to provide a clear picture regarding the implementation of PSAK 45. The results of this research indicate that the NTB Transportation Service uses SAP 01 guidelines in preparing its financial reports, and has not presented several financial reports in accordance with SAP 01 or PSAK 45.